Revised environmental identity scale: Adaptation and preliminary examination on a sample of Italian pet owners - Ariccio, S.; Mosca, O. (Frontiers in Psychology, 2023)
The Revised Environmental Identity Scale is a tool proposed by Clayton in 2021 to replace her 2003’s Environmental Identity Scale and aims at measuring individual differences in a stable sense of interdependence and connectedness with nature. Since an Italian version of this scale was still missing, the present paper presents an adaptation of the Revised Environmental Identity Scale in Italian. The scale has been translated, back-translated, and administered online to 163 pet owners living in Italy in the context of a study about pet attachment. A parallel analysis suggested the existence of two factors. The exploratory factor analysis identified the same number of factors: “Connectedness to nature” (9 items) and “Protection of nature” (5 items); the two sub-scales were found to be consistent. This structure explains more variance compared to the traditional one-factor solution. Socio-demographic variables do not seem to affect the scores of the two Environmental identity factors. This adaptation and preliminary validation of EID scale has relevant implications for studies in the Italian context as well as on specific population groups such as pet owners, and, more generally, for international studies on environmental identity.